Performance optimization of Maisotsenko cycle heat exchangers: A three-dimensional parametric analysis - Seyed Esmail Razavi; Tohid Adibi; Mohanad Naji Halool Abohned; Shams Forruque Ahmed; Hammad Alotaibi (Case Studies in Thermal Engineering)
The Maisotsenko cycle (M-cycle) heat exchangers have emerged as a promising technology due to their potential for high heat transfer rates and sustainable cooling. However, previous studies have lacked comprehensive three-dimensional modeling to evaluate the effects of geometry, relative humidity, and airflow on heat exchanger performance. To address this gap, this study presents an optimized performance analysis of M-cycle heat exchangers using OpenFOAM. The research examines the impact of key parameters, including fluid flow rate, inlet humidity, and channel geometry, on heat transfer efficiency. Results indicate that reducing inlet humidity and increasing flow rate improves heat transfer, while channel geometry is critical to performance. Higher humidity in both the wet and dry channels minimizes the effectiveness of the heat exchanger. Additionally, parallel flow configurations outperform counter-flow setups, showing an 18 % higher efficiency and a 20 % increase in the Nusselt number. The efficiency of the heat exchanger ranged between 0.54 and 0.73, underscoring the importance of optimizing design parameters for different operating conditions. These findings offer valuable insights into addressing global energy efficiency challenges and advancing climate control technologies, providing practical guidance for engineers and researchers in sustainable cooling solutions.